Peran Ketokohan Pangeran Santri dalam Penyebaran Agama Islam di Wilayah Kerajaan Sumedang Larang - Ainun Nisa Rosiana; Muhammad Ana Nasarudin; Perawati Perawati; Najwa Kamila; Najwa Zakia Akmal; Andi Annisa Anggraeni; Zaharah Zaharah (Jurnal Kabar Masyarakat, 2026)
This study examines the role of Prince Santri (Prince Kusumadinata I) in the process of Islamization in the territory of the Kingdom of Sumedang Larang. The formulation of the problem includes the role of leadership, socio-cultural impact, the values taught, and the community's response to the spread of Islam. The research uses a qualitative method with a descriptive-historical approach, through observation, interviews, and documentation in the area of the Tomb of Prince Santri (Pasarean Gede), Sumedang Regency. The results of the study show that Islamization takes place through a top-down pattern, where Prince Santri first convinces Ratu Dewi Inten Dewata (Ratu Pucuk Umun) before the teachings of Islam are spread to the wider community. Da'wah is carried out peacefully through friendship, while the marriage of Prince Santri with Ratu Pucuk Umun becomes a mechanism of routine charisma that institutionalizes Islam into the royal structure. This strategy allowed Islam to survive and develop even after the death of Prince Santri. The findings of the study confirm that the Islamization of Sumedang Larang is not only religious, but also political and cultural, with the integration of Islamic values into the royal order. This research contribution enriches the local Islamic historical literature by showing how charismatic leadership and peace strategies can accelerate the process of Islamization in the context of traditional kingdoms.